INTERFACE MATTERS: A MIXED-METHODS STUDY ON DIGITAL AND TRADITIONAL READING MODALITIES IN ESL UNIVERSITY CONTEXTS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This study compares digital and traditional reading formats in an ESL university setting, focusing on reading comprehension and strategy use. Thirty upper-intermediate learners were split into two groups to read texts using either e-books or printed materials. Comprehension outcomes were similar across both groups. However, the print group used more support strategies, like highlighting and note-taking, while the e-book group favored bilingual dictionary tools but underused features like annotations. Many e-book users, initially unfamiliar with digital reading, developed a preference for it after guided use. The study concludes that format does not affect comprehension significantly, but the reading interface shapes strategy behavior. Teachers should provide training to help students use e-book features effectively.